Bioethics in the practice of colposcopy - Jerónimo, José (2021)
The objective of this presentation is to encourage gynecology and obstetrics specialists to reflect on the ethical management of all their cases and clinical procedures, ensuring that their professional performance is in line with scientific knowledge, evidence-based medicine and respect for the principles of bioethics. We present the case of a 20-year-old patient who underwent several cervical cancer screening and diagnostic tests that triggered a surgical recommendation. A clinical and ethical analysis of the case is made, and recommendations are given for appropriate management guided by evidence and national and international recommendations.